Economic Analysis of The Utilization of Palm Kernel Shell Waste As An Alternative Fuel For Coal Substitution in Power Plants - Wahyu Isnanda Nasution; Jamilah; Eva Wardah; Setia Budi; Zuriani; Riani (Universitas Medan Area, 2026)
This study aims to analyze the potential utilization of palm kernel shell waste as an alternative fuel to replace coal in steam power plants. The method used is a literature study with a descriptive and comparative approach based on various previous studies. The analysis was conducted by comparing energy characteristics through calorific value, electricity generation capability represented by the energy ratio, and economic aspects reflected in fuel prices and energy costs.The results show that palm kernel shells have an average calorific value of approximately 4,300 kcal/kg, which is relatively close to medium-grade coal with an average value of around 5,000 kcal/kg. In terms of electricity generation capability, the energy ratio of palm kernel shells ranges from 0.935 to 1.160 MW/ton, while coal ranges from 1.158 to 1.724 MW/ton. Although coal demonstrates relatively higher energy efficiency, palm kernel shells exhibit a significant economic advantage due to their lower fuel price, resulting in energy costs of approximately IDR 906,000–925,000 per MW, compared to coal which ranges from IDR 1,434,000–1,456,000 per MW. Therefore, palm kernel shells have strong potential as an alternative fuel that is technically feasible and more economically efficient, particularly in regions with abundant availability of palm oil waste.